Creative India: Tapping the full potential - Prateek Kukreja; Havishaye Puri; Dil Bahadur Rahut (Asian Development Bank Institute (ADBI), 2022)
India's creative economy is large, but its untapped potential is even larger. This study provides the first reliable measure on the size of India's creative economy, explores the many challenges faced by the creative industries, and provides recommendations to make India one of the most creative societies in the world. India's creative economy-measured by the number of people working in various creative occupations-is estimated to contribute nearly 8% of the country's employment, much higher than the corresponding share in Turkey (1%), Mexico (1.5%), the Republic of Korea (1.9%), and even Australia (2.1%). Creative occupations also pay reasonably well-88% higher than the non-creative ones and contribute about 20% to nation's overall GVA. Out of the top ten creative districts in India, six are non-metros-Badgam (J&K), Panipat (Haryana), Imphal (Manipur), Sant Ravi Das Nagar (Uttar Pradesh), Thane (Maharashtra), and Tirupur (Tamil Nadu)-indicating the diversity and depth of creativity across India. Yet, according to United Nations Conference on Trade and Development, India's creative exports are only one-tenth of those of the People's Republic of China. To develop the creative economy to realize its full potential, Indian policymakers would like to: (i) increase the recognition of Indian culture globally; (ii) facilitate human capital development among its youth; (iii) address the bottlenecks in the Intellectual Property (IP) framework; (iv) improve access to finance; and (v) streamline the process of policymaking by establishing one intermediary organization. India must also leverage its G20 Presidency to put creative economy concretely on the global agenda.
Keywords: J21; J24; J31; O10; O30; O53; Z10; 330; creative economy; culture; employment; output; intellectual property; G20